(3GdJbhje GdOhGei GdbeQis - (3CHh ESeGYjd jhSa MSjf Hf GdbGVi eMeO GdMSf GdNGfHhQi GdgfOis ((3HdOI GdeSGf s)
(3ChdgG (B:s
(3CbSe GdSfI GdgLQjI Ydi (B( 30) (3hGVQH GdNGQL ai (B( 5) (3hGbSe GdMGUd Ydi (B( 7 s
(3BNQgG (B:s
(3jfJgi HGdLOhd GdePchQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(1095) s
Keywords: (3GdeLGejYs